Open World Cause : Morse summer project - Wilkinson, Garrett (My University, 2015)
Our research piece was composed of demographic questionnaires, community interviewing, and conversations with Govinda Panthy, conducted for the purpose of gathering information on local social, economic, historical, and political contexts. I created our demographic questionnaire from a previous survey administered by Nepal’s Ministry of Health (funded by USAID). What follows are a few of our notable findings from the questionnaire. We found that approximately half (or more) of the students at the school suffered from waterborne disease on a regular basis during the monsoon season. The most common source of water was from unprotected wells and, in the dry season, open bodies of water. We learned that the local health post had rehydration therapy solutions available for those with diarrhea. We also learned that either due to pesticides or genetically modified crops, poorer families no longer had to go hungry due to bad yields. In the past five years, all families have gained access to a personal toilet, and most families now wash their hands. Very few families had bank accounts or financial savings, and about the same number of adults had finished high school. However, we found that younger generations were increasingly more likely to stay in school for longer periods of time. Our community interviewing consisted of open-ended questions that also allowed for the collection of qualitative data. An example of insights gained from this is that every single low-income family wanted school lunches provided to their children at school (something that isn’t always common in the area). In fact, we found that some of the poorer students were embarrassed to eat their packed lunches in front of other students because they were aware that their food was of lower quality. Because of this knowledge, the school, Tripur Kinder Academy, now has a school lunch program. All students eat the same food and have access to fruits and vegetables. The conversations we had with Govinda Panthy, the school director, yielded insights that have become crucial to the efficacy of our partnership with him and his staff. Many cross-cultural misunderstandings have been cleared away, and both parties have a better understanding of one another now that we have lived together for a summer.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Wilkinson, G. (2016). Open World Cause : Morse summer project. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Open World Cause (Organization); Education, Bilingual--Nepal; Education, Rural--Nepal; Rural development--Nepal; Reports; Reports